(3GdNdY Hjf GdTQjYI hGdbGfhfs - (3YWjI, RjfH YHO GdMGaX CMeOs ((3GdbGgQI (B:s (3LGeYI GdCRgQ,s, 2004)
(3jJfGhd GdcJGH bVjI GdNdY aj GdTQjYI hGdbGfhf(B.s
Keywords: (3GdNdY (B((3GdWdGb(B)s; (3GdWdGb (B((3abg ESdGej(B)s; (3GdNdY (B((3GdWdGb(B)s -- (3bhGfjf hJTQjYGJs -- (3eUQs